Floristic composition of government degree and PG College Campus, Wanaparthy, Mahabubnagar District, Telangana - Sadasivaiah, B.; Goud, M. Sharath; Devilal, R.; Laxmikanth, M.; Kumar, M. Uday; Ramakrishna, A.; Swaroopa, V.; Narasimha, A.; Shirisha, C.; Reddy, M. Sridhar (International Journal of Environment, 2016)
The floristic components of Government Degree and PG College campus, Wanaparthy yield 355 plant taxa including 15 endemics at various levels. The results also showed that, good number of medicinal plants, wild relatives, fodder plants and wild edible plants. The results indicated that the college campus is very rich in plant diversity which is very useful to the student community for their study. International Journal of Environment Vol. 5 (1) 2016, pp: 45-66